Community Behavior Regarding the Control of Dengue Hemorrhagic Fever in East Nusa Tenggara: Literature review - Sali, Tredesia Eda; Landudjama, Leni; Toru, Veronika (Poltekkes Kemenkes Kupang, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus through the bite of the Aedes sp mosquito with Aedes aegypti as the main vector and Aedes albopictus as the secondary vector. The number of DHF sufferers in East Nusa Tenggara (NTT) Province increased until 2020, with 4,518 people infected and 48 people died. This research aims to determine the description of community behavior regarding disease control (DHF) in East Nusa Tenggara. Method: Using literature review research with problem identification stages, data search using Google Scholar, Science Direct, ProQuest databases with the keywords